(untitled) (CAHIERS MAGELLANES-NS, 2024)
The development and evaluation of Flunarizine oral thin films as an alternative dosage form were undertaken to enhance patient compliance, especially for individuals with difficulty swallowing tablets or capsules. The formulation aimed to provide a rapid onset of action and a convenient, portable drug delivery system. Various formulations (F1–F9) were prepared and characterized for key parameters such as general appearance, thickness, weight, folding endurance, disintegration time, tensile strength, moisture content, drug content assay, and in-vitro drug release. The films exhibited uniformity in appearance, and consistent thickness and weight, indicating the reproducibility of the formulation process. The folding endurance of the films was excellent, and the disintegration time was fast, ranging from 48 to 85 seconds, which is suitable for quick drug release upon contact with saliva. The drug assay showed consistent drug content in the films, ensuring accurate dosing. In-vitro drug release from the optimized formulation (F7) demonstrated rapid release, with 99.05% of Flunarizine released by the 10th minute. Kinetic studies revealed that the drug release followed the Peppas model, indicating a non-Fickian diffusion mechanism. The stability study showed that the drug content remained stable over three months, confirming the formulation’s potential for long-term storage. This study suggests that Flunarizine oral thin films are a promising alternative dosage form for providing rapid therapeutic effects with improved patient compliance.